2013
DOI: 10.1007/s12028-013-9908-0
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of 30-Day Readmission After Subarachnoid Hemorrhage

Abstract: Demographics, severity of neurologic injury, radiographic cerebral infarction, and outcomes were not associated with readmission after SAH. Markers of a more complicated hospital course (ICU and hospital LOS, EVD placement) were associated with 30-day readmission. Most readmissions were for infections acquired after discharge. Readmission within 30 days is difficult to predict, and, since the most common reason was infection acquired after discharge, it may be difficult to prevent without an integrated health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 20 publications
1
28
0
Order By: Relevance
“…Although several studies have attempted to identify risk factors for readmission, such efforts alone are insufficient to understand the utility of rehospitalization as a quality metric and to identify targets for improved patient care. 20,28 To complement these quantitative approaches, qualitative analyses have been used for a variety of conditions to identify the causes underling readmission, including potential lapses in care and unavoidable disease progression. 9,22,25,33 In this study, we qualitatively analyzed the unique factors leading to rehospitalization after aneurysmal SAH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies have attempted to identify risk factors for readmission, such efforts alone are insufficient to understand the utility of rehospitalization as a quality metric and to identify targets for improved patient care. 20,28 To complement these quantitative approaches, qualitative analyses have been used for a variety of conditions to identify the causes underling readmission, including potential lapses in care and unavoidable disease progression. 9,22,25,33 In this study, we qualitatively analyzed the unique factors leading to rehospitalization after aneurysmal SAH.…”
Section: Discussionmentioning
confidence: 99%
“…29 Although 30-day readmission has begun to be used as a quality marker in SAH research, 19 most studies investigating readmission in stroke patients have focused on ischemic etiologies, and, therefore, evidence describing the causes underlying rehospitalization after SAH is lacking. 6,20,21,30 While small-scale efforts have been made to identify predictors of readmission after SAH, 28 the reasons for readmission, including both medical/surgical diagnoses and underlying root causes, remain unknown. Stakeholders need such information to determine the extent to which readmission reflects deficiencies in clinical care and subsequently plan quality improvement initiatives to address potential shortcomings.…”
mentioning
confidence: 99%
“…In another study, 2 among patients with no angiographic evidence of SAH, 75% experienced severe headache during their inpatient stay, and 25% experienced persistent headache at a mean follow-up of more than 24 months after discharge. The results of a prospective study 14 published in 2013 indicated that headache was the second-leading cause for 30-day hospital readmission after SAH. Long-term follow-up data indicate that headache may persist after SAH for 2 to 9 years.…”
mentioning
confidence: 99%
“…Prior analyses are limited by focusing on patient‐level characteristics and in‐patient mortality . A single‐center study found most readmissions after aSAH were related to infections or symptomatic hydrocephalus . A population‐based study found no difference in mortality or readmission rates between clipping and endovascular coiling among older patients with aSAH .…”
mentioning
confidence: 99%
“…There is only limited understanding of the hospital-level determinants of 30-day readmission and mortality after aSAH among older patients. Prior analyses are limited by focusing on patient-level characteristics [7][8][9] and in-patient mortality. [10][11][12] A single-center study found most readmissions after aSAH were related to infections or symptomatic hydrocephalus.…”
mentioning
confidence: 99%